THE ROLE AND SIGNIFICANCE OF VIRTUAL ASSETS IN CYBERCRIMES - Goyibkulov Obidjon Orolovich (Western European Studies, 2024)
The legal and forensic aspects of the collection and use of virtual traces in the investigation of crimes committed using information technologies are considered. Modern investigative practice in identifying and investigating cybercrimes is analyzed. The problems arising in the investigation of cybercrimes are explored.
Keywords: cybercrime; virtual traces; digital evidence